2021
DOI: 10.3390/biom11081171
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Skeletal Muscle Secretome Reveals a Role for Extracellular Vesicles and IL1α/IL1β in Restricting Fibro/Adipogenic Progenitor Adipogenesis

Abstract: Repeated mechanical stress causes injuries in the adult skeletal muscle that need to be repaired. Although muscle regeneration is a highly efficient process, it fails in some pathological conditions, compromising tissue functionality. This may be caused by aberrant cell–cell communication, resulting in the deposition of fibrotic and adipose infiltrates. Here, we investigate in vivo changes in the profile of skeletal muscle secretome during the regeneration process to suggest new targetable regulatory circuits … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 68 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…Importantly, Madaro and colleagues et al ( Madaro et al, 2018 ) detected increased IL-1β in FAPs after denervation, further suggesting that IL-1β is a component of the FAP secretome that is stimulated with disuse. Most recently, Vumbaca and colleagues showed that IL-1β played an important role in the skeletal muscle secretome ( Vumbaca et al, 2021 ). The FAP secretome includes some factors that are anabolic such as WISP1, which induces satellite cell expansion and differentiation ( Lukjanenko et al, 2019 ; Zhang et al, 2020 ), and follistatin, which induces myoblast differentiation and inhibits myostatin ( Amthor et al, 2004 ; Mozzetta et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Madaro and colleagues et al ( Madaro et al, 2018 ) detected increased IL-1β in FAPs after denervation, further suggesting that IL-1β is a component of the FAP secretome that is stimulated with disuse. Most recently, Vumbaca and colleagues showed that IL-1β played an important role in the skeletal muscle secretome ( Vumbaca et al, 2021 ). The FAP secretome includes some factors that are anabolic such as WISP1, which induces satellite cell expansion and differentiation ( Lukjanenko et al, 2019 ; Zhang et al, 2020 ), and follistatin, which induces myoblast differentiation and inhibits myostatin ( Amthor et al, 2004 ; Mozzetta et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have demonstrated that these enzymes may be released by damaged muscle [41][42][43] . The mechanism(s) by which the enzymes enter the blood may combine leakage through sarcolemma wounds, exocytosis, extracellular vesicles [44][45][46] and activity-dependent lymph flow 47,48 .…”
Section: Sarcolemma Damage In Exercisementioning
confidence: 99%
“…TNF-α, which is highly secreted by pro-inflammatory macrophages during acute injury, was shown to be the effector of FAPs apoptosis [ 54 ]. Another pro-inflammatory factor secreted by pro-inflammatory macrophages, IL-1α/β, was also shown to inhibit adipogenic differentiation of FAPs [ 64 ]. As the regeneration process progresses, there is a switch in macrophage phenotype towards anti-inflammatory macrophages, which secrete higher levels of TGF-β.…”
Section: Faps Cellular and Molecular Crosstalk In Regenerating Skeletal Musclementioning
confidence: 99%
“…In vitro experiments showed that myoblast conditioned medium promotes FAPs proliferation. Satellite cells were shown to secrete betabellulin and epidermal growth factor (EGF), two ligands of the EGF receptor (EGFR), which stimulate FAPs proliferation in vitro [ 64 ]. Notably, contrary to myoblast conditioned medium, myotube-conditioned medium inhibits the expression of adipogenesis genes and upregulates the expression of fibrogenesis genes, suggesting that factors secreted during late stage of myogenesis could impact on the cell fate decision of FAPs and ECM remodelling [ 17 , 80 ].…”
Section: Faps Cellular and Molecular Crosstalk In Regenerating Skeletal Musclementioning
confidence: 99%